APPLICABILITY ANALYSIS OF HEXAHEDRAL HOLLOW PROFILES AS COMPONENT ELEMENTS OF SUPPORTING SYSTEMS FOR GONDOLA CARS - Fomin, O. V. (Science and Transport Progress, 2014)
Purpose. The purpose of work is presentation of features and results of the conducted works on determination of introduction expedience of hexahedral hollow profiles as the component elements of the modern supporting systems of railway freight gondola cars. Methodology. During the research an introduction methodology of different types of profiles as alternative to the existent supporting elements of the body module for freight car was used. This methodology had been developed by the author before. It is oriented to the reduction in material consumption and providing of strength requirements and operating reliability of the car design under study. The developed methodology includes the procedures of admissible values calculation of the resistance moments of the section of the hexahedral hollow profile, which is being introduced. It also includes the determination of optimum (i.e. characterized by the minimum material consumption when meeting the durability requirements) values of height and minimum thickness of profile in the conditions of construction limitations. At the same time the admissible resistance moments are calculated as such, which are equal to the value of existent implementation of supporting element or as such that are determined taking into account the surplus design reserve. The first direction is applied in this work. Findings. As a result of the conducted research the introduction expedience of hexahedral hollow profiles as vertical rods of the lateral and latitude belts of the walls of the butt-end freight gondola cars is grounded and the optimum parameters of such replacements are determined. Originality. The problem of the use expedience of hexahedral hollow profiles as the supporting elements of the freight gondola cars bodies was first considered in the article. To solve this problem the mathematical models describing the dependence of basic strength and mass indexes of the proper profiles on varying the geometrical parameters, as well as the auxiliary graph are developed. Practical value. Practical implementation of the results of conducted research for universal freight gondola cars will reduce their empty weight and accordingly increase their lifting capacity for almost 100 kg. upon the implementation of durability and operating reliability requirements. This taking into account the large scale of their park will provide a considerable economic effect at their producing and operation. The materials developed and presented in the article can be used for consideration and solution of analogical tasks for other types of freight cars, and also for other facilities of the transport engineering. According to the results of the work an invention application of Ukraine was applied.